PEMANFAATAN LAHAN TANAMAN CABAI BAGI UMKM DALAM MENINGKATKAN PEREKONOMIAN DI AMBARAWANG DARAT, KABUPATEN KUTAI KARTANEGARA, KALIMANRAN TIMUR - Azizil Yudaruddin, Yanzil; Ramadhani, Ranita; Karlinda Sari , Dika; Juwari, Juwari; Della Ananda Lesmana, Siti (Fakultas Ekonomi Universitas Balikpapan, 2022)
Due to its high economic value, chili (Capsicum annum L.) horticultural commodities are in great demand. As the population and industry increase, the need for chili as a raw material also increases, as does the need for chili every year. In Jember Regency, red chili productivity is also low, only 87.68 quintals hectare-1. Several factors cause fluctuations in red chili production in the Kutai Kartanegara region, including unfavorable environments such as low soil fertility, high pest attacks, and excessive use of pesticides. As a result, agricultural development is needed to meet food needs and expand export opportunities to neighboring countries. Secondary data derived from land unit maps provide the parameters observed in this study. Setting the spacing, applying organic matter, agricultural lime, fertilizing phosphorus (P), as well as cutting and backfilling the soil with a mound or bench terrace system to reduce soil erosion are corrective steps to increase the land suitability class. Secondary data includes soil drainage, soil depth in cm, slope associated with erosion, elevation, waterlogging, and soil cation exchange capacity.